Efficacy and Safety of Vildagliptin in New‐Onset Diabetes After Kidney Transplantation—A Randomized, Double‐Blind, Placebo‐Controlled Trial. Issue 1 (26th November 2013) - Haidinger, M.; Werzowa, J.; Hecking, M.; Antlanger, M.; Stemer, G.; Pleiner, J.; Kopecky, C.; Kovarik, J. J.; Döller, D.; Pacini, G.; Säemann, M. D.
<x xml:space="preserve">Abstract</x> New‐onset diabetes after transplantation (NODAT) is a serious complication after kidney transplantation, but therapeutic strategies remain underexplored. Dipeptidyl peptidase‐4 (DPP‐4) inhibitors selectively foster insulin secretion without inducing hypoglycemia, which might be advantageous in kidney transplant recipients (KTRs) with NODAT. We conducted a randomized, double‐blind, placebo‐controlled, phase II trial to assess safety and efficacy of the DPP‐4 inhibitor vildagliptin. Intraindividual differences in oral glucose tolerance test (OGTT)‐derived 2‐h plasma glucose (2HPG) from baseline to 3 months after treatment served as primary endpoint. Among secondary outcomes, we evaluated HbA1c, metabolic and safety parameters, as well as OGTTs at 1 month after drug discontinuation. Of 509 stable KTRs who were screened in our outpatient clinic, 63 (12.4%) had 2HPG ≥200 mg/dL, 33 of them were randomized and 32 completed the study. In the vildagliptin group 2HPG and HbA1c were profoundly reduced in comparison to placebo (vildagliptin: 2HPG = 182.7 mg/dL, HbA1c = 6.1%; placebo: 2HPG = 231.2 mg/dL, HbA1c = 6.5%; both p ≤ 0.05), and statistical significance was achieved for the primary endpoint (vildagliptin: 2HPG‐difference −73.7 ± 51.3 mg/dL; placebo: −5.7 ± 41.4 mg/dL; p < 0.01). Adverse events were generally mild and occurred at similar rates in both groups. In conclusion, DPP‐4 inhibition in KTRs with overt NODAT was safe and efficient, providing a novel treatment alternative for this specific form of diabetes.